Evaluación del rediseño de los sistemas de levantamiento artificial por bombeo electrosumergible presentes en un campo de la cuenca del Valle Medio del Magdalena para la optimización de la producción de hidrocarburo. (2023)
The work below seeks to generate an optimization of hydrocarbon production for a field located in the Valle Medio del Magdalena basin, by proposing redesigns in its artificial lift system by electro-submersible pumping. With a sample of 22 wells, the current state of each one was evaluated by means of simulation in the Pipesim software, which allowed knowing those wells in which the electro-submersible pumps were operating in Downthrust or Upthrust ranges. Once identified and selected, we proceeded to simulate each of the proposed redesign scenarios defined as: variation in the number of stages, variation in the operating frequency, and change in the electro-submersible pump.